THE STUDY OF AMINOACID AND VITAMIN COMPOSITION OF CERATOCEPHALA FALCATA’S ABOVE-GROUND PART (Scientific journal of the Fergana State University, 2023)
In this article, using HPLC (High performance liquid chromatography), based on known methods, the content of amino acids and vitamins in the wild plant Ceratocephala falcata, collected from the pastures of the “Kurama” mountain range of our country, was studied. A total of 20 amino acids and 6 water-soluble vitamins have been identified. It has been established that 1 gram of the plant contains approximately 2.85 mg of amino acids and 2.28 mg of water-soluble vitamins. The largest amount of amino acids falls on aspartic acid (0.490532 mg/g), and the smallest on threonine (0.00578 mg/g). Among vitamins, vitamin C makes up the most amount (0.569523 mg/ml) and vitamin PP the least (0.067715 mg/ml).